2006
DOI: 10.1159/000094152
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcomes of Pediatric Traumatic Brain Injury

Abstract: Traumatic brain injury is a leading cause of death and disability in the pediatric age group. Causes of injury vary with child developmental age, with more inflicted injuries in infants, fall-related injuries among toddlers, sports-related injuries among middle-school-aged children and motor vehicle crashes in older children. Prevention strategies exist for some pediatric traumatic brain injury; however, all suffer from lack of compliance and enforcement. Neuropsychological and behavioral outcomes for injured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
138
1
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(161 citation statements)
references
References 101 publications
7
138
1
10
Order By: Relevance
“…45,52 Recent evidence has shown that older teens generally demonstrate better outcomes than younger children, perhaps due to greater vulnerability among younger children to more severe physical injury. 3,4,28,32 Despite these factors, however, children overall tend to have better clinical outcomes following TBI than adults. 3,4,28 To investigate the reasons for such differences in outcomes, many animal models have been used to compare young versus old age and TBI.…”
Section: Differences In Tbi Within the Pediatric Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…45,52 Recent evidence has shown that older teens generally demonstrate better outcomes than younger children, perhaps due to greater vulnerability among younger children to more severe physical injury. 3,4,28,32 Despite these factors, however, children overall tend to have better clinical outcomes following TBI than adults. 3,4,28 To investigate the reasons for such differences in outcomes, many animal models have been used to compare young versus old age and TBI.…”
Section: Differences In Tbi Within the Pediatric Populationmentioning
confidence: 99%
“…3,4,28,32 Despite these factors, however, children overall tend to have better clinical outcomes following TBI than adults. 3,4,28 To investigate the reasons for such differences in outcomes, many animal models have been used to compare young versus old age and TBI. Studies have examined the role of biomechanics, 35 metabolism, 43 cell death, 9,25 electrophysiology, 17,44 and glutamatergic neurotransmission 23,24 as possible mechanisms to explain the improved clinical outcome in pediatric compared with adult patients.…”
Section: Differences In Tbi Within the Pediatric Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial injury is a leading cause of mortality and morbidity in children. 6 A skull fracture may be an indicator of intracranial injury; hence, an accurate diagnosis in pediatric head trauma is important.…”
mentioning
confidence: 99%
“…Unique to pediatrics is inflicted traumatic brain injury (iTBI), a major cause of TBI in young patients [17]. Inflicted injury is associated with worse outcome compared to accidental trauma and represents a disproportionate number of deaths in the patients 2 years of age [18][19][20][21]. Different biomechanical mechanisms of injury, exposure to multiple repeated insults, younger age of patients, and secondary injury factors, such as hypoxia and seizures, have all been proposed as potential factors.…”
Section: How Is Tbi Different In Children?mentioning
confidence: 99%